Viewing the Sparkling Scenery of the Sea with Μαρμάρεος (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2020)
Bright sea-views, their mysteriously multicoloured, resonant motion empowered with a sense of divinity, enchant viewers. One element is crucial; the significance of the light that brightens and darkens marine hues. Focusing on μαρμάρεος, through a colour-related epistemological approach, I examine μαρμάρεος’ metaphorical, transformed representation, illuminating the entangled interrelation between its bright-hued aspects and viewers. The view of sparkling sea at Il. XIV 273 is challenging to visualise, since colour, being co-involved with various factors, is a multisensory experience. Also, neuroscientific research indicates the positive benefit for humans of being near the sea, including viewing marine vistas. Distilling the unseen nexus between μαρμάρεος, light, and sea, which entails a two-fold connotation, my goal is to reveal the poet’s aesthetic, almost orchestral skill, conveying both visual effect and the sacredness of light, unveiling the ancient colour-sense.